Adoption of opioid-prescribing guidelines in primary care: a realist synthesis of contextual factors - Nora Jacobson; Bri Deyo; Andrew Quanbeck; Roberta A Johnson; Christie Schlabach; Jillian Incha; Lynn Madden; Daniel Almirall; Rose Hennessey Garza; Nicholas Schumacher; Christine Stephenson (BMJ Open)
Objective As part of an effort to design an implementation strategy tailoring tool, our research group sought to understand what is known about how contextual factors and prescriber characteristics affect the adoption of guideline-concordant opioid-prescribing practices in primary care settings.Design We conducted a realist synthesis of 71 articles.Results We found that adoption is related to contextual factors at the individual, clinic, health system and environmental levels, which operate via intrapersonal, interpersonal, organisational and structural mechanisms.Conclusion A single static model cannot capture the complexity of the relationships between contexts, mechanisms and outcomes. Instead, a deeper understanding requires a dynamic model that conceptualises clusters of contextual factors and mechanisms that tend towards guideline concordance and clusters that tend toward non-concordance.Trail registration number ClinicalTrial.gov registration number NCT04044521.